Influence of the Flipped Classroom Learning Model and Student Learning Styles on Student Learning Outcomes - Yahya, Muhammad Ridzky Abidzar; Abidin, Zainul; Husna, Arafah (Proceedings Series of Educational Studies, 2024)
Based on the results of observations of teacher-centered learning activities, during teaching and learning activities in class students are not actively involved and the interaction between teachers and students in the learning process is still not implemented well. Therefore, a solution is needed to overcome this problem, namely finding an effective way to improve student learning outcomes in the learning process. The purpose of this research is to find out what the learning model is Flipped Classroom and learning styles influence student learning outcomes. This research presents the results of data obtained by students of SMP Plus Al-Kautsar Malang City in 2024 in the science learning process. This research also presents data in the form of learning outcomes for class VII students in the learning process using the learning model Flipped Classroom and Learning Style (Visual, Auditory, Kinesthetic). The method used in this research is Quasi Experimental Design with a quantitative approach and research design